PHYSICAL-MECHANICAL PROPERTIES AND PERMEABILITY EVALUATION OF CHITOSAN FILM - Endang Warsiki, Juanda Sianturi dan Titi Candra Sunarti (Department of Agroindustrial Technology, Bogor Agricultural University, 2011)
ABSTRACTThe aim of this study was to compare the physical-mechanical properties between the packaging film made from chitosan with the garlic extract and the conventional packaging of polypropilene (PP). Garlic extract addition in this film resulted higher thickness and elongation at break compared to the film without garlic extract. However, the film has less strength than others. The results also showed that the properties of break of films based on chitosan were better than those of the commercial film. However, in some other properties, i.e. strength and water vapour transmission rate, PP was still superior than chitosan film. The chitosan film could be easily sealed as good as PP. That means that some part of the films properties is comparable to PP. So far, chitosan film resulted from this study had good prospect as a material to substitute conventional packaging material, such as PP. In addition, the effect of the drawback in permeability could be reduced by adding inert gases or sealing the product in vacuum condition or putting it as secondary or tertiary packaging.Keywords: packaging film, chitosan, garlic extract, polypropylene